2018
DOI: 10.1177/1057567718799829
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Property Crime: Does Absolute Inequality Matter?

Abstract: Economic crime models and the social strain theory argue that income inequality can foster property crime, yet empirical studies do not provide strong support for this relationship across countries. An important limitation of these studies is that they only consider relative inequality measures and omit absolute ones. Absolute inequality can have a crime-inducing effect for two main reasons: First, the potential monetary returns from crime can be expected to depend on the interaction between relative income in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…Academic literature has extensively examined the effect of inequality on crime, primarily focusing on the most violent criminal typologies. A significant portion of these investigations agrees that an increase in inequality is positively correlated with the rise in violent crimes (Constantini et al, 2018;Fajnzylber et al, 2002;Goda and García, 2019;Kang, 2016;Rowhani-Rahbar et al, 2019). Among these studies, those that assert that countries or societies with high levels of inequality tend to have a higher homicide rate stand out (Blau and Blau, 1982;Enamorado et al, 2016;Li et al, 2019;Nivette, 2011;Ouimet, 2012;Santos et al, 2018;Torres Téllez, 2022;Wilkins et al, 2019).…”
Section: The Effects Of Inequality On Crime: a Review Of The Issuementioning
confidence: 95%
“…Academic literature has extensively examined the effect of inequality on crime, primarily focusing on the most violent criminal typologies. A significant portion of these investigations agrees that an increase in inequality is positively correlated with the rise in violent crimes (Constantini et al, 2018;Fajnzylber et al, 2002;Goda and García, 2019;Kang, 2016;Rowhani-Rahbar et al, 2019). Among these studies, those that assert that countries or societies with high levels of inequality tend to have a higher homicide rate stand out (Blau and Blau, 1982;Enamorado et al, 2016;Li et al, 2019;Nivette, 2011;Ouimet, 2012;Santos et al, 2018;Torres Téllez, 2022;Wilkins et al, 2019).…”
Section: The Effects Of Inequality On Crime: a Review Of The Issuementioning
confidence: 95%
“…Faktor ekonomi negatif menjadi insentif kriminalitas berkurang hanya jika faktor ekonomi negatif tersebut diantisipasi. Contoh faktor ekonomi negatif yang diantisipasi adalah tingkat pengangguran (Buba et al, 2018;Ishak & Bani, 2017;Khan et al, 2015), tingkat kemiskinan (Diaw et al, 2014;Opeyemi Oyelade, 2019;Pare & Felson, 2014;Song et al, 2020), dan ketimpangan ekonomi (Buba et al, 2018;Goda & Torres García, 2019;Grover, 2013;Heimer, 2019;Lobonţ et al, 2017).…”
Section: Gambar 1 Produksi Barang Legal Dan Kriminalunclassified
“…Imran et al [72] argue that poverty leads to property crime in the long run in the USA. In an across-countries study, Goda and Torres García [76] empirically concluded that absolute income inequality is a more significant and robust determinant of violent property crime than relative inequality. A cross-national study showed that income inequality has little or no effect on crime in Western/Southern Europe [77].…”
Section: Spatial Analyses Of the Coefficientsmentioning
confidence: 99%